The Influence Of Organizational Communication On Job Satisfaction Of State Civil Apparatus At The Regional Secretariat Of Bekasi City - Rimayanti Wardani; Rizka Yuanita (Community Engagement and Emergence Journal (CEEJ), 2024)
Effective organizational communication plays a crucial role in creating a healthy and productive work environment, especially in the public sector, which is expected to deliver optimal public services. In the context of civil servants (ASN), open and structured communication is believed to enhance employee job satisfaction. This study aims to analyze the influence of organizational communication on the job satisfaction of civil servants at the Regional Secretariat of Bekasi City. A quantitative approach was used with a simple linear regression technique. The number of respondents was 136, selected through proportional random sampling. The analysis results show that organizational communication has a positive and significant effect on job satisfaction, with a significance value of 0.000 and a coefficient of determination of 29.7%. These findings reinforce the understanding that effective internal communication can improve employee job satisfaction within the bureaucracy.